Principles of environmental chemistry - Harrison, Roy M., 1948- (RSC Pub., 2007)
Environmental chemistry is becoming increasingly important and is crucial in the understanding of a range of issues, ranging from climate change to local pollution problems. Principles of Environmental Chemistry draws upon sections of the authors' previous text (Understanding our Environment) and reflects the growing trend of a more sophisticated approach to teaching environmental science at university. This new, revised text book focuses on the chemistry involved in environmental problems. Written by leading experts in the field, the book provides an in depth introduction to the chemical proc.